120 CARDIOTROPHIN 1 EXPRESSION IN THE NEONATAL BRAIN FOLLOWING FOCAL CEREBRAL ISCHEMIA. (1st January 2006) - Wen, T. C.; Rogido, M.; Moore, J. E.; Peng, H.; Sola, A.
Abstract : Background: Cardiotrophin 1 (CT-1), a gp130 ligand and an inflammation mediator, was initially found to induce hypertrophy of neonatal cardiac myocytes in vitro. Subsequent studies have shown that CT-1 also protects neonatal ventricular myocytes and isolated rat cardiac myocytes against apoptosis caused by serumdeprivation or stress stimuli when added before simulated ischemia or during reoxygenation in vitro. Recent studies demonstrate that CT-1 acts as a neuroprotectant for motor, sensory, and sympathetic neurons in the peripheral nervous system. To date, however, a role for CT-1 neuroprotection within the central nervous system (CNS) has not been clearly demonstrated. In addition, it is unknown if there is CT-1 expression within the CNS after stroke. Objective: To determine if there is CT-1 expression within the brain after focal cerebral ischemia (FCI) in the postnatal day 7 (P7) rat. Methods: FCI was induced by an intraluminal catheter technique causing middle cerebral artery occlusion in P7 rats, as we have previously described. The rat pups were sacrificed at 1, 3, 6, 12, 24, and 72 h after FCI, and then their brains were collected and prepared for Western blot and immunohistochemistry analyses with an antimouse CT-1 antibody. Recombinant human CT-1 was used as a positive control for Western blot analysis. Results: Western blot analysis showed a single weak band corresponding to CT-1 in the nonischemic right cortex. The intensity of CT-1-positive bands began to increase in the ischemic left cortex from 3 h after FCI. Densitometric analysis showed that CT-1 protein was significantly increased in the ischemic left cortex from 6 to 24 h after FCI compared with the corresponding nonischemic right cortex (p < .05, tested by analysis of variance followed by a post hoc test of Fisher's protected LSD). At 72 h after FCI, CT-1 expression in the ischemic left cortex did not increase significantly, although the mean inverted gray value in the ischemic left cortex was higher than in the nonischemic right cortex. Subsequent immunohistochemistry analysis showed that many CT-1-positive cells were detected both in the periphery and in the center of the ischemic cortex 12 h after FCI. In addition, CT-1 was found on some small blood vessels within the ischemic left cortex. Conclusion: This study is the first demonstration that FCI induces a rapid increase in the expression of CT-1 protein within the ischemic cortex of the P7 rat brain. Future work will need to examine if this increased CT-1 expression is associated with a neuroprotective effect within the CNS.